2020
DOI: 10.35680/2372-0247.1408
|View full text |Cite
|
Sign up to set email alerts
|

Patient education in the hospital-at-home care context

Abstract: The objective of this study is to describe adult patients' and their family caregivers' experiences of patient education in the hospital-at-home care context. Methods included a cross-sectional descriptive study including three hospital-at-home units in Finland. Adult, non-palliative patients (n = 27) and their family caregivers (n = 18) were interviewed pairwise by telephone, and the data analyzed with inductive thematic content analysis. COREQ guidelines were used to plan and guide the study design. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For instance, the qualitative survey 10 showed that societies' understanding and interpretation of HHC can affect the HHC utilization modes; therefore, individuals must receive general training on HHC. Vaartio-Rajalin et al 23 likewise reported that when HHC recipients are unaware of their rights, they become uncertain about the choices they make and the future that lies ahead. This problem reduces their satisfaction and negatively affects their future choices.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the qualitative survey 10 showed that societies' understanding and interpretation of HHC can affect the HHC utilization modes; therefore, individuals must receive general training on HHC. Vaartio-Rajalin et al 23 likewise reported that when HHC recipients are unaware of their rights, they become uncertain about the choices they make and the future that lies ahead. This problem reduces their satisfaction and negatively affects their future choices.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals play a key role in hospitals' health education initiatives: they analyze patients' skills in health literacy and propose medical information that satisfies patients' needs in terms of knowledge and emotional support (Navarro, 2020). Thanks to this patient-centered education approach, patients reinforce their empowerment and establish better relationships with health professionals (Vaartio-Rajalin, Nyholm, Fagerström, 2020). On the other hand, health professionals measure their patients' empowerment in different ways: analyzing their behaviours and prejudices, and implementing continuous monitoring systems (Navarro Martínez, Igual García, Traver Salcedo, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empowered patients decide whether to be treated or not, whether to be hospitalized or not, and whether to be active or not; being empowered does not necessarily imply making decisions on a health topic that is related to the guidelines imposed by health professionals [ 18 ]. Thanks to empowerment, patients and their relatives reinforce their rights [ 26 ].…”
Section: From Patients’ Education To Health Education Based On Mobile...mentioning
confidence: 99%
“…More and more hospitals are resorting to mobile apps to implement advanced patient education programs that ensure person-centered care [ 26 ]. These programs are especially useful for patients suffering from non-communicable diseases such as diabetes, cancer, heart disease, or chronic respiratory disease.…”
Section: From Patients’ Education To Health Education Based On Mobile...mentioning
confidence: 99%